Small punch creep performance of heterogeneous microstructure dominated Inconel 718 fabricated by selective laser melting. (October 2020) - Wang, L.Y.; Wang, Y.C.; Zhou, Z.J.; Wan, H.Y.; Li, C.P.; Chen, G.F.; Zhang, G.P.
Abstract: Creep performance of additively-manufactured components is strongly related to additive manufacturing process-induced microstructures and loading direction. Here, the creep life and the cracking behavior of Inconel 718 fabricated by selective laser melting were investigated systematically at 650°C and 400 N by means of the small punch creep testing method. The results show that the periodic and spatially heterogeneous microstructures composed of V-shaped grains and columnar grains are produced, and play an important role in the creep performance. Under the same heat-treatment condition, the creep resistance of the specimens loaded along the scanning direction is much higher than that of the ones loaded along the building direction. While under the same loading direction, homogenization/aging-treated specimens have the longest creep life and the solution/aging-treated specimens are of the shortest creep life. The creep cracking mechanism of the alloy associated with the spatially heterogeneous microstructures was elucidated. The theoretical calculation suggests that the higher energy input or the larger overlap ratio of the melting pools may decrease the area fraction of the V-shaped grains to enhance the creep life. The finding provides a potential strategy to design microstructures for the high creep performance of selective laser melting-fabricated Inconel 718. Graphical abstract: Unlabelled Image Highlights: Spatially heterogeneous microstructures in Inconel 718 were produced by selective laser melting process. Creep resistance is strongly associated with the loading direction and heat-treatment strategy. Creep cracking mechanisms were elucidated based on the spatially heterogeneous microstructures and loading directions. A higher energy input or a larger overlap ratio of melting pools is helpful in enhancing the creep life.